2021
DOI: 10.3389/fmed.2021.681169
|View full text |Cite
|
Sign up to set email alerts
|

Oral Scutellarin Treatment Ameliorates Retinal Thinning and Visual Deficits in Experimental Glaucoma

Abstract: Purpose: Intraocular pressure (IOP) is currently the only modifiable risk factor for glaucoma, yet glaucoma can continue to progress despite controlled IOP. Thus, development of glaucoma neurotherapeutics remains an unmet need. Scutellarin is a flavonoid that can exert neuroprotective effects in the eye and brain. Here, we investigated the neurobehavioral effects of scutellarin treatment in a chronic IOP elevation model.Methods: Ten adult C57BL/6J mice were unilaterally injected with an optically clear hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Tree shrews may be considered as an alternative glaucoma animal model given the presence of the laminar cribrosa in the eyes of these small animals ( 27 ). The ability to access refined measurements of glaucoma pathology in a longitudinal and non-invasive manner could improve the usability of these models moving forward ( 91 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tree shrews may be considered as an alternative glaucoma animal model given the presence of the laminar cribrosa in the eyes of these small animals ( 27 ). The ability to access refined measurements of glaucoma pathology in a longitudinal and non-invasive manner could improve the usability of these models moving forward ( 91 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…7-O-Methylisomucronulatol was key compound in the compound-target network of Qing Guang An Granule (QGAG) to the treatment of glaucoma [ 36 ]. Scutellarin was discovered as a substance that protects the nerves of the eyes and brain, which is a new neurotherapeutic agent for glaucoma treatment, it has been studied in mice, at present, [ 37 , 38 ]. Acetylsalicylic acid has complex effects on the changes of intraocular pressure, studies have demonstrated that single-use of acetylsalicylic acid cannot significantly reduce intraocular pressure in glaucoma patients, but long-term use will have an impact on intraocular pressure [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scutellarin also has pharmacological activities such as treatment of glaucoma, liver protection, kidney protection, and hyperuricemia. Zhu et al established a mouse model of glaucoma and found that scutellarin could maintain the retinal structure and visual function of mice when intraocular pressure was elevated, suggesting that scutellarin is a potentially novel neurotherapeutic agent used in the treatment of glaucoma [ 90 ]. Li et al found that scutellarin reduced renal injury and lowered the glomerular filtration rate in hyperuricemic mice (HN), which may be alleviated by a regulatory mechanism of extracellular cellular communication network factor 1 (CCN1) on the activation of NLRP3 inflammatory vesicles [ 91 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%